Content analysis of kfcku application: hyperreality interface - A Abdi; Budi Prayogi; Meiana Harfika; Rahmat; Melda Agnes Manuhutu (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Digital application becomes key role in delivering great services from big franchise such as Pegadaian, Tix ID, Shopee, Netflix, etc. The digital application on KFCku app had recently been helping in building digital payment. Hyperreality becomes widespread practice in this industry as they continue to live day by day. The core concept of this research is Hyperreality which influences substantial number of people into purchasing stuff. Purchasing should by your own decision instead of someone’s making. Content analysis will be a useful technique to measure how strong the enemy is.